PF-23 Canine Pancytopenia with Normocytic-Normochromic Anemia: Case Reports in Three Dogs [2016-2017] - L Maylina; D Sajuthi; S Widodo; A Esfandiari; S D Widhyari; R Wulansari; R P A Lelana; A Wijaya; C Choliq; A P Mihardi; S Komariah; R C Saleh; J Dumayanti (Hemera Zoa, 2018)
Canine pancytopenia is a disease that occurs in dogs caused by a decrease in the number of erythrocytes, leukocytes and thrombocytes/platelets in the blood. Canine pancytopenia often attacks dogs that live in the tropic climates. The diseases can be caused by an agent infection, excessive cell proliferation and through an immune intermediary. A decreasing in the number of erythrocytes followed by a decreasing of hemoglobin and hematocrit causes anemic condition. Non-regenerative anemia that often occurs when pancytopenia is normocytic-normochromic anemia [1].